The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00701-011-1122-2
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone inhibits ICAM-1 and MMP-9 expression and reduces brain edema in intracerebral hemorrhagic rats

Abstract: In conclusion, these data show that DEX successfully reduced post-stroke brain edema by decreasing MMP-9 and ICAM-1 levels, partially through the IκB/NF-κB signaling pathway. The timing of DEX administration in relation to the onset of brain injury may be critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 32 publications
5
31
0
3
Order By: Relevance
“…The mechanism by which neutrophils, macrophages and lymphocytes enter the brain after ICH has received much less attention. Several studies have shown an upregulation of intercellular adhesion molecule-1 (ICAM-1) after experimental ICH [92,101,104] and Rolland et al . found that fingolimod blocked both ICAM-1 upregulation and lymphocyte transmigration into brain [101].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which neutrophils, macrophages and lymphocytes enter the brain after ICH has received much less attention. Several studies have shown an upregulation of intercellular adhesion molecule-1 (ICAM-1) after experimental ICH [92,101,104] and Rolland et al . found that fingolimod blocked both ICAM-1 upregulation and lymphocyte transmigration into brain [101].…”
Section: Introductionmentioning
confidence: 99%
“…Patients treated with fingolimod have a higher Glasgow Coma Scale score, lower National Institutes of Health Stroke Scale score, improved neurologic function and fewer ICH-related lung infections without differences in the occurrence of adverse events when compared with the control group. Dexamethasone can promote the recovery of ICH injury by inhibiting the inflammatory response and reduce brain edema because of its capacity to decrease apoptotic cell death and inhibiting the intercellular adhesion molecule-1 and MMP-9 expression [10,84] .…”
Section: Inhibition Of Pmns Infiltration and Microglia Activationmentioning
confidence: 99%
“…Interestingly, dexamethasone used to attenuate brain edema in the clinic downregulated VEGF and MMP-9 levels in vitro and in vivo experimental models. 17,71) Thus, the anti-edema effects of dexamethasone may involve ameliorating BBB disruption that is commonly observed in TBI, cerebral ischemia, and hemorrhage, and which leads to lethal conditions including brain edema, severe inflammatory damage, and hemorrhage. Thus, protection of the BBB must be a beneficial strategy for these pathophysiological conditions and a broad spectrum of brain damage.…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of CAMs and chemokines evaluated after brain damage were reported to accelerate leukocyte infiltration. [15][16][17] Infiltrating leukocytes migrate into areas of damage and release various cytokines, chemokines, reactive oxygen species (ROS) and proteases that cause brain tissue damage.…”
Section: Inflammationmentioning
confidence: 99%